Workshop Store Room Improvement With 5s: A Case Study - A. P., Puvanasvaran (2012)
Implementing the 5S technique at workshop store room to solve the problems observed is the main focus of this paper. In order to achieve the main purpose of the study, four specific objectives have been defined. First, is to understand the concept and theories of 5S. Second, to observe the problems occurred in the workshop store room. Third, implement 5S technique which consists of 5 pillars: sorting, set in order, shines, standardizes and sustains to solve the problems occurred at the workshop store room. Finally, measure the improvement at workplace area after implementing 5S technique.